Factors influencing success: Secondary cytoreductive surgery in the management of recurrent ovarian cancer - Yi, Huixing; Zeng, Rongdong; Lv, Xiaogang (Molecular & Cellular Biomechanics, 2024)
Objective: Secondary cytoreductive surgery (SCRS) plays a key role in the treatment of ROC. The aim of this study was to provide an in-depth analysis of the practical application of SCRS in the management of recurrent ovarian cancer (ROC) and to assess the specific impact of its therapeutic effect on the long-term prognosis of patients. Methods: We collected clinicopathologic data on 83 ROC patients who received SCRS from January 2010 to January 2020, including patient age, histological type, and SCRS results. Kaplan-Meier survival curve, Logistic regression test and Cox proportional risk model were used for univariate regression analysis. Results: We ended up with a detailed analysis of 80 patients. During the observation period, up to the prescribed end of follow-up, 26 patients were observed to be alive, while 57 patients had died. The mean survival of all patients was 56 months. The clinical factors affecting progression-free survival were neoadjuvant chemotherapy [HR (95% CI) = 1.40 (1.13–1.74)], The recurrence interval [HR (95% CI) = 0.51 (0.36–0.70)], previously used chemotherapy line number [HR (95% CI) = 1.46 (1.17–1.82)], recurrence period to the total number of cycles of chemotherapy [HR (95% CI) = 3.48 (2.65–4.57)]. Factors affecting the degree of SCRS completion include tumor stage [HR (95% CI) = 2.723(1.281–5.786)], tumor size [HR (95% CI) = 0.386 (0.153–0.896)], The number of tumors [HR (95% CI) = 2.893 (1.056–7.925)]. Conclusion: Tumor stage, time interval of recurrence, size and number of lesions are closely related to the success rate of SCRS. Recurrent ovarian cancer patients achieve complete elimination of tumor cells through SCRS to optimize treatment outcomes and prognosis.